A comparative experimental study on emission characteristics of a turbocharged gasoline direct-injection (TGDI) engine fuelled with gasoline/ethanol blends under transient cold-start and steady-state conditions. (1st October 2020) - Guo, Tao; Duan, Xiongbo; Liu, Yiqun; Liu, Jingping; Zhou, Xianjie; Li, Yangyang; Lai, Ming-chia; Guo, Genmiao
Abstract: In this study, the emissions of a TGDI engine were experimentally investigated and compared under transient cold-start operating and steady-state operating conditions, respectively. Furthermore, the steady-state emissions of the TGDI engine under different coolant out temperature (43 °C, 65 °C, 88 °C, 102 °C and 110 °C) were compared to the transient emissions. The results indicated that the transient NOx emissions and the steady-state NOx emissions were strongly depended on the load of the TGDI engine. Moreover, under steady-state operating conditions, the NOx emissions of the TGDI engine were increased with the coolant temperature from 43 °C to 102 °C, while the NOx emissions were decreased at the outlet coolant temperature of 110 °C due to retard the spark timing. Apart from that, the HC emissions under transient cold-start condition were approximately ten times than that of the steady-state conditions. Under steady-state operating conditions, the HC emissions were basically decreased with the coolant temperature from 43 °C to 110 °C due to reduction of the flame quenching distance. The excess air ratio of the TGDI engine slightly fluctuated around stoichiometric air/fuel ratio under the NEDC, while the excess air ratio was literally off the charts during the deceleration operating conditions due to the fuel cut-off. CO emission periodically reached a peak value at deceleration operating conditions under transient cold start condition, while CO emission was much high at the high-load and high-speed regions under steady-state operating conditions. In addition, the outlet coolant temperature did not present an obvious effect on the CO emission formation.